The influence of trehalose, taurine, cysteamine and hyaluronan on ram semen -: Microscopic and oxidative stress parameters after freeze-thawing process - Bucak, Mustafa Numan; Atessahin, Ahmet; Varish, Omer; Yuce, Abdurrauf; Tekin, Necmettin; Akcay, Aytac (Elsevier Science Inc, 2007)
There is a lack of information regarding lipid peroxidation and antioxidant capacity in cryopreserved ram semen, and cryopreservation is associated with the production of reactive oxygen species (ROS) which lead to lipid peroxidation (LPO) of sperm membranes, resulting in a loss of motility, viability and fertility of sperm. The aim of this study was to determine the influence of certain additives and their different doses on standard semen parameters, lipid peroxidation and antioxidant activities after the cryopreservation/thawing of ram semen. Ejaculates collected from four Akkaraman rams, a native breed of sheep, were evaluated and pooled at 33 degrees C. Semen samples which were diluted with a Tris-based extender containing additives including trehalose (50, 100 mM), taurine (25, 50 mM), cysteamine (5, 10 mM), and hyaluronan (0.5, 1 mg/ml), and an extender containing no additives (control) were cooled to 5 T and frozen in 0.25 ml French straws, being stored in liquid nitrogen. Frozen straws were thawed individually at 37 degrees C for 20 s in a water bath for evaluation. The use of a Tris-based extender supplemented with 50 mM trehalose, 25 mM taurine, and 5 and 10 mM cysteamine led to higher percentages of post-thaw motility, in comparison to the control group (P < 0.01). No significant differences were observed in the percentages of acrosome and total abnormalities, and the hypoosmotic swelling test upon the supplementation of the freezing extender with antioxidants after the thawing of semen. In biochemical assays, the addition of antioxidants did not cause significant differences in levels of malondialdehyde (MDA), glutathione (GSH), and glutathione peroxidase (GSH-Px), after thawing, when compared to groups with no additives. In this study, catalase (CAT) activities were higher in the group that was applied 25 mM taurine as an antioxidant, than in all of the other groups (P < 0.001). Compared to the controls, antioxidant treatment with 100 mM trehalose, 50 mM taurine, 5 mM cysteamine and 0.5 mg/ml hyaluronan, significantly elevated vitamin E (vit E) levels in samples (P < 0.001). Published by Elsevier Inc.
Keywords: ram semen; freezing; additives; semen parameters; antioxidant activities